Association of Thyroid Antibodies with Occurrence of Hypothyroidism after Radio-iodine Therapy in Patients with Graves’ Disease Attending a Tertiary Level Hospital of Bangladesh - Chaudhary, Amardeep; Jabin, Zeenat; Selim, Shahjada; Naznin, Afroza; Hasan, Mizanul (Bangladesh Journal of Nuclear Medicine, 2024)
Background: Graves’ disease (GD) is an autoantibody-mediated autoimmune disease caused by direct stimulation of the thyroid epithelial cells. Thyrotropin Receptor Antibody and Thyroid Peroxidase Antibody are among the best-characterized autoantibodies for this pathology. Among different treatment modalities, radioiodine therapy (RAIT) is a proven safe and highly cost-effective therapeutic option, with the frequent side effect of developing hypothyroidism. Serum concentrations of various autoantibodies before and after RAIT may be used to predict the early or late onset of hypothyroidism. Objective: To measure and statistically analyze the thyrotropin receptor antibody (TRAb) and thyroid peroxidase antibodies (TPOAb) in a group of hyperthyroid patients who did or did not develop early hypothyroidism after RAIT. Patients and methods: This prospective comparative study was conducted at the thyroid division of the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between March 2020 and June 2021. The study population was selected from diagnosed adult Graves. disease patients. A detailed history was taken, and a clinical examination was done for each patient. High-resolution ultrasound of the neck, thyroid scan, radioactive iodine uptake test, FT3, FT4, TSH, TPOAb, and TRAb were done one month before RAIT. After that, all patients were treated with a modified fixed dose of radioiodine (131I) orally. Post-therapy follow-ups were done at the 3rd, 6th, and 9th months after therapy, during which serum FT3, FT4, TSH, TPOAb, and TRAb were estimated. Result: Out of 60 enrolled patients, 54 completed their scheduled visits. They were divided into two groups based on the early (within three months) or late (after three months) occurrence of hypothyroidism after therapy. There was no significant difference observed between the two groups regarding gender, age, duration of disease, or 131I dose. No significant difference was noted between the pre-therapy serum FT3, FT4, and TSH levels of group A and B patients. At the third month, all three parameters were significantly different between the groups. But at 6 months, a significant statistical difference was observed between the groups regarding serum FT3 and TSH but not FT4. The TPOAb was found to be significantly higher in group A before therapy and in each follow-up. However, TRAb was significantly higher in group A only at the 6-month follow-up. Conclusion: Higher levels of serum TRAb and TPOAb in patients with Graves. disease at diagnosis are closely associated with the occurrence of early hypothyroidism. Bangladesh J. Nuclear Med. 26(2): 167-171, 2023